First Report of a Phytoplasma Strain in the Elm Yellows Group (16SrV) associated with Virginia Creeper in Maryland, USA - Padmanabhan, Chellappan; Nunziata, Schyler; Kim, Bo Min; Rivera, Yazmin; Costanzo, Stefano (Plant disease, 2024)
Virginia creeper ( [L.] Planch.) is a deciduous flowering vine in the Vitaceae family. Native to eastern North America, it is often used ornamentally as a climbing vine or as ground cover due to its rapid growth and foliage color in the fall. In July of 2022, along exterior walls of a private property in Lanham, MD, two Virginia creeper (VC) vines were observed displaying symptoms of yellow mottling and premature reddening of leaves. To investigate the cause of these symptoms, two symptomatic leaf samples and one asymptomatic leaf samples from a third vine in the same vicinity were collected for further analysis. A Qiagen DNeasy Plant Mini Kit was used to extract total DNA from leaf tissues according to the manufacturer's instructions. A phytoplasma-specific real-time PCR (Hodgetts et al. 2009) was used to test the DNA extracts, which detected the presence of phytoplasmas in the two DNA samples derived from symptomatic vines. The near full-length of the 16S ribosomal RNA gene was then amplified by seminested PCR from these samples with primers P1/16S-SR followed by P1A/16S-SR (Deng, and Hiruki 1991; Lee et al. 2004) and Sanger sequenced using primers P1A and 16S-SR. Analysis of the obtained 16S rDNA sequences revealed no variation between the two plant samples, and one sequence was deposited in GenBank representing the phytoplasma strain named VC-MD1 (GenBank PP746981). A BLASTn search of the 16S rRNA gene sequence in the NCBI nucleotide database, showed 99.93% sequence identity with the phytoplasma strain AldY-WA1 (GenBank MZ557341) from red alder in Washington, a phytoplasma associated with VC plants in southern Florida (GenBank AF305198) (Harrison et al. 2001), and other strains detected in grapevines in Europe described as "flavescence dorée" phytoplasma (GenBank AF176319) (Davis, and Dally 2001). The virtual restriction fragment length polymorphism pattern derived from PhyClassifier (Zhao et al. 2009), indicated that VC-MD1 is indeed a member of the 16SrV-C phytoplasma subgroup. To confirm the identification, the partial operon and the partial gene were amplified as previously described (Lee et al. 2010; Makarova et al. 2012). Specifically, the operon region was amplified using a nested PCR approach with primer set L15F1A-a/MapR1 followed by L15F1A-b/MapR1A-b. Sequence data obtained from the two loci were deposited to GenBank with accession numbers PP746982 ( ) and PP746983 ( ). BLAST searches querying the nucleotide sequences of the operon and gene showed 95.39% and 99.05% identity, respectively, to the corresponding loci of ' Phytoplasma rubi' strain RS (GenBank CP114006) and hemp dogbane yellows phytoplasma strain HD1 (GenBank FR686506). Phylogenetic analysis based on and gene sequences suggest that the VC-MD1 strain is evolutionary closest to 16SrV-C phytoplasma strains detected in various hosts in the United States, including HD1 and AldY-WA1. These North American strains cluster together on a distinct branch within the elm yellows group phytoplasmas. For the State of Maryland, this detection represents the first report of a phytoplasma strain member of the16SrV-C subgroup infecting VC plants. A phytoplasma of the same subgroup was previously detected in Florida in asymptomatic VC vines (Harrison et al. 2001). The 16S rRNA gene sequences of the two VC phytoplasma strains are nearly identical, differing by just a single nucleotide. The disease transmission vectors of the VC-MD1 strain and the prevalence of the disease in the region remains undetermined.